Development of a model for environmentally responsible behavior intention - Tresuk, Worrapot; Leamlaksakul, Bharisa; Piamsirikamol, Bongkotrat; Soonsan, Nimit (KKBS Journal of Business Administration and Accountancy, 2025)
This research examines the influence of corporate social responsibility on hotel customers’ environmentally responsible behavior, focusing on the mediating roles of perceived value and environmental awareness. Data were collected from 346 hotel customers in Phuket, Thailand, using structured questionnaires and analyzed via partial least squares structural equation modeling (PLS-SEM). The results showed that corporate social responsibility (CSR) has no direct effect on environmentally responsible behavior (ERB) or perceived value. CSR significantly enhances environmental awareness, which fully mediates the CSR-ERB relationship. Perceived value positively influences both environmental awareness and ERB. These results suggest that hotels should integrate corporate social responsibility initiatives with value-driven communication and awareness campaigns to effectively promote sustainable behaviors. The study advances the literature by empirically validating the sequential mediation mechanism in the hospitality context.